Human exposure to polyhalogenated hydrocarbons and incidence of selected malignancies - central European experience - Bencko, Vladimír; Rameš, Jiří; Ondrušová, Martina; Pleško, Ivan; Juřičková, Lenka; Trnovec, Tomáš (Neoplasma, 2009)
This paper describes results of two ecological studies design to analyze the incidence of selected malignancies in two populations exposed to polychlorinated hydrocarbons, mostly PCBs and TCDDs/Fs by comparing data available in the National Cancer Registry of the Slovak Republic and National Oncological Registry of the Czech Republic databases for the Slovak Republic (approximately 5M inhabitants) and the Czech Republic (10,3 M inhabitants) to the data relevant for the population of Michalovce District, the Slovak Republic (approximately 112,000 inhabitants) and Uherske Hradiste, the Czech Republic (146,000 inhabitants). Those districts are recognized as PCB-contaminated areas due to production and industrial use of PCBs. Data were analyzed for the 10-year period 1987-1996. The age adjusted world standard ratio (WSR) incidence of thyroid, pancreatic, breast, ovarian, bladder, and brain tumors in females and thyroid, pancreatic, breast, bladder, brain, prostate and testicular tumors in males were compared. Neither PCBs nor TCDDs/Fs appear to contribute to the observed significantly lower incidence of breast and prostate cancer in the Michalovce District and lower bladder cancer incidence in Uherske Hradiste District. However, anti-estrogenic and anti-androgenic properties have been described for hydroxylated and methylsulfonyl PCB metabolites. These properties could contribute to a mechanism through which these metabolites might modulate the development of breast, prostate and bladder cancer. The results of our analysis points to substantial potential problems of risk assessment for cancer incidence in populations exposed to xenobiotics, or more generally, as it relates to a wide spectrum of confoundings of cancer risk factors.
Keywords: Female; Europe; Polychlorinated Biphenyls; ženské pohlaví; Neoplasms; nádory; polychlorované bifenyly; polychlorované dibenzodioxiny; Slovakia; lidé; Evropa; Carcinogens; Risk Factors; Incidence; Male; incidence; karcinogeny; rizikové faktory; vystavení vlivu životního prostředí; Slovenská republika; mužské pohlaví; Environmental Exposure; Polychlorinated Dibenzodioxins; Humans